ChemInform Abstract: CoBi3: A Binary Cobalt‐Bismuth Compound and Superconductor. Issue 52 (24th December 2013) - Schwarz, Ulrich; Tence, Sophie; Janson, Oleg; Koz, Cevriye; Krellner, Cornelius; Burkhardt, Ulrich; Rosner, Helge; Steglich, Frank; Grin, Yuri
Abstract The title compound is prepared from mixtures of the elements (5 GPa, 720 K, 95% yield) and characterized by powder XRD, electrical measurements, and DFT band structure calculations.